The Story of the B-52s - Creney, Scott. author. aut Link
XII, 256 p. 25 illus., 3 illus. in color.
Keywords: The Story of the B-52s: Neon Side of Town is the first critical biography of one of the most unique popular bands in American music. The B-52s were far more than just a “tacky dance band.” Their aesthetic was shaped by the radical social and political conditions in Athens, Georgia, and their arrival in New York City profoundly influenced the next several years of music and art to come out of that city. The Story of the B-52s provides a deep critical analysis of the band’s music and original insights into the extraordinary people who made it. Their story, told here in full for the first time, contains all the elements of a great novel—success and failure, tragedy and triumph, life and death. Yet, at the heart of the B-52s music is a love for being alive that verges on the radical.